Determination of the withdrawal period of enrofloxacin in guinea pigs (Cavia porcellus) - Ortiz G., Tomás (2022)
The aim of this study was to determine the period of withdrawal of enrofloxacin in guinea pigs (Cavia porcellus). In total, 51 guinea pigs (25 females and 26 males) of the Peru breed from a farm located in the district of Maranganí (Cusco, Peru) were used. For this, 10% enrofloxacin was administered orally at a rate of 10 mg/kg (0.1 ml/kg BW) every 24 hours for a period of 10 days. Immediately after the last administration of the antibiotic (hour 0), three guinea pigs were randomly selected and slaughtered every 2 hours until 32 hours after drug withdrawal, taking samples of the diaphragm muscle. The analysis and quantification of antibiotic residues in the muscle was performed using the commercial Max Signal® Enrofloxacin ELISA Kit. The maximum concentration of enrofloxacin (1425 ± 53.4 µg/kg) was determined 12 h after withdrawal, falling to 80.8 ± 6 µg/kg at 28 h, value below 100 µg/kg considered as the reference maximum residue limit. Under the conditions of this study, a withdrawal period of two days is suggested for guinea pigs treated with enrofloxacin.